Defining competence profiles in obstetrics and gynecology using the modified requirement tracking questionnaire - Baptiste Tarasi; Viktor Oubaid; David Baud (BMC Medical Education)
Abstract Background Data about the competencies needed for physicians in obstetrics and gynecology (O&G) is currently insufficient. The aim of this study is to define the competence profile needed in this sector for daily professional activity, in order to account for these criteria in future recruitment. Methods The modified requirement-tracking questionnaire (R-track) was sent to 307 physicians working in the field of O&G with different training levels and practice locations. The R-track is designed to assess professional competence profiles and contains 66 items covering the following eight competence areas: “Mental abilities”, “Social sensibility”, “Psychomotor and multitasking abilities”, “Solutions orientation”, “Social interactive competences”, “Personality traits”, “Verbal competences” and “Resistance capacity”. The mean scores of single items and competence areas were calculated. Results were compared between gender, training level, and place of practice. Results The participation rate was 65.5%, with 201 physicians returning the questionnaire. In this sample, 50.2% of them were in training and 49.8% were practicing O&G specialists. The proportion of physicians working in a hospital setting was 64.7% while 30.3% worked in private practice. The competence areas “Social sensibility” and “Psychomotor & multitasking abilities” appear to be the most important for daily professional activity. At the item level, “Stress resistance”, followed by “Workload management” and “Tactfulness” were considered as the most valuable characteristics. Differences between gender, level of training, and place of practice were not significant. Conclusion The identified competence profile could serve as a basis for developing a new method of O&G residency selection. In addition, such a profile could help medical students to decide on a professional specialization at a very early stage by comparing their personal competence profile with the one in the field or with their mentors.